2019
DOI: 10.12973/eu-jer.8.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Mathematical Concept Skills of Children Trained with Montessori Approach and MoNE Pre-school Education Program

Abstract: In this study, it is aimed to examine the mathematical conceptual skills of 48-72-month-old children attending pre-school education institutions providing a Montessori Approach and Ministry of Education Pre-school Program (MoE PSP). The study group consisted of 20 children, who were trained by the Montessori Approach, and 20 children, who continued to attend pre-school education institutions applying the MoE PSP. The research was carried out in accordance with the state study design of the qualitative research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…A difference was observed between the two educational approaches in favor of the Montessori education. In the literature, studies comparing Montessori approach to and other educational approaches, showed cognitive skills related to reasoning skills were more developed among children in a Montessori program (Ahmadpour & Mujembari, 2015;Durkaya, 2019;Lillard, 2012;Ongoren, 2008;Ongoren & Yazlik, 2019). Drenckhahn (1961) also illustrated that the mathematics materials used in Montessori education supported children's logical thinking.…”
Section: Discussionmentioning
confidence: 99%
“…A difference was observed between the two educational approaches in favor of the Montessori education. In the literature, studies comparing Montessori approach to and other educational approaches, showed cognitive skills related to reasoning skills were more developed among children in a Montessori program (Ahmadpour & Mujembari, 2015;Durkaya, 2019;Lillard, 2012;Ongoren, 2008;Ongoren & Yazlik, 2019). Drenckhahn (1961) also illustrated that the mathematics materials used in Montessori education supported children's logical thinking.…”
Section: Discussionmentioning
confidence: 99%
“…Holfester (2018) argues that concepts such as textbooks, exams, grades, rewards or punishments only provide a dependent instruction. Cooperation rather than competition among children (Colgan, 2016;Gross & Rutland, 2019) should be transmitted to educate for humanity, offering children the right to participate in their educational development as it benefits their social participation processes (Correia et al, 2019;Ongoren & Yazlik, 2019).…”
Section: Review Of Early Childhood Education: Facilitating Factors Bmentioning
confidence: 99%
“…One key aspect of this approach is where education takes place: a prepared environment designed and created to cater for children of different ages. Spatial adaptations are based on this particular methodology and affect the quality of education (Chan, 1988;İslamoğlu, 2017) as materials are created and set to stimulate children's interests and skills (Ongoren & Yazlik, 2019). Kirk and Jay (2018) note that the creation of a prepared environment is defined as the structure (physical) and process (psychological) where children increase their knowledge as creative and critical people who emancipate their talents freely (İslamoğlu, 2017), and drive to virtuosity unobstructed by adult praise or judgement (Lillard, 2018).…”
Section: Montessori Environmentmentioning
confidence: 99%
See 1 more Smart Citation